Effects of psychological priming, video, and music on anaerobic exercise performance - Loizou, G.; Karageorghis, C. I. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Peak performance videos accompanied by music can help athletes to optimize their pre-competition mindset and are often used. Priming techniques can be incorporated into such videos to influence athletes' motivational state. There has been limited empirical work investigating the combined effects of such stimuli on anaerobic performance. The present study examined the psychological and psychophysiological effects of video, music, and priming when used as a pre-performance intervention for an anaerobic endurance task. Psychological measures included the main axes of the circumplex model of affect and liking scores taken pre-task, and the Exercise-induced Feeling Inventory, which was administered post-task. Physiological measures comprised heart rate variability and heart rate recorded pre-task. Fifteen males (age 26.3 ± 2.8 years) were exposed to four conditions prior to performing the Wingate Anaerobic Test: music-only, video and music, video with music and motivational primes, and a no-video/no-music control. Results indicate that the combined video, music, and primes condition was the most effective in terms of influencing participants' pre-task affect and subsequent anaerobic performance; this was followed by the music-only condition. The findings indicate the utility of such stimuli as a pre-performance technique to enhance athletes' or exercisers' psychological states